Post-prandial reactive hypoglycaemia and diarrhea caused by idiopathic accelerated gastric emptying: a case report - Middleton, Stephen J (BioMed Central, 2011)
INTRODUCTION: The majority of cases of post-prandial reactive hypoglycemia are considered idiopathic. Abnormalities of B-cell function and glucose regulation by insulin and glucagon have been postulated as causes but associated gastrointestinal dysfunction has not been reported. We report the first case of accelerated gastric emptying associated with post-prandial reactive hypoglycemia, abdominal bloating and diarrhea. We consider that gastric dysmotility is an important cause of this condition as treatment of the underlying abnormal gastric emptying allows effective control of symptoms. CASE PRESENTATION: A 20-year-old Caucasian woman presented with post-prandial fatigue, sweating, nausea, faintness and intermittent confusion, which had led to pre-syncope and syncope on occasions. She also experienced marked abdominal bloating and diarrhea over the same period. These episodes responded to oral administration of sweet drinks. Her symptoms were ameliorated by modification of her diet. CONCLUSION: This is an original case report of the association of idiopathic accelerated gastric emptying with post-prandial reactive hypoglycemia and diarrhea. Family physicians, endocrinologists and gastroenterologists often consult patients with a constellation of post-prandial symptoms, which are considered to be idiopathic in most cases. This case indicates that gastric dysmotility might be the primary cause of these symptoms in some patients and, if found, offers a therapeutic target which in our case was successful.